2018
DOI: 10.3389/fneur.2018.00048
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Visual Stimuli on Stability and Complexity of Postural Control

Abstract: Visual input could benefit balance control or increase postural sway, and it is far from fully understanding the effect of visual stimuli on postural stability and its underlying mechanism. In this study, the effect of different visual inputs on stability and complexity of postural control was examined by analyzing the mean velocity (MV), SD, and fuzzy approximate entropy (fApEn) of the center of pressure (COP) signal during quiet upright standing. We designed five visual exposure conditions: eyes-closed, eyes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 28 publications
4
25
0
2
Order By: Relevance
“…In our study, challenging VE led to more pronounced postural perturbation in SP than in HA, which is consistent with their strong reliance on visual information [5]. Furthermore, in contrast to other studies evaluating the effect of VR on postural control [12,13,15], we proposed a multiple complex task with various optical flow induced by changing the density and avoidance space of avatars in a crowded environment. All in all, we suggest that immersive and various ecological virtual environment conditions can be used in SP virtual reality rehabilitation programs with progressive challenging situations.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In our study, challenging VE led to more pronounced postural perturbation in SP than in HA, which is consistent with their strong reliance on visual information [5]. Furthermore, in contrast to other studies evaluating the effect of VR on postural control [12,13,15], we proposed a multiple complex task with various optical flow induced by changing the density and avoidance space of avatars in a crowded environment. All in all, we suggest that immersive and various ecological virtual environment conditions can be used in SP virtual reality rehabilitation programs with progressive challenging situations.…”
Section: Discussionsupporting
confidence: 86%
“…Previous work indicates that static virtual environments (VE) do not appear to challenge postural control [12,13] whereas dynamic scenes induce postural perturbations in healthy young adults (HA) [12] and older adults [14]. However, D'Antonio et al [15] reported lesser postural perturbations in SP and older HA compared with young HA in semi-immersive environment.…”
Section: Introductionmentioning
confidence: 99%
“…Visual information may lead to both abnormal postural control of the body and its improvement [29]. In our study, the elimination of visual control resulted in higher COP path length values compared to the open eye study in the experimental and control group.…”
Section: Resultsmentioning
confidence: 44%
“…The result showed significant differences in the sway velocity between with and without VR environments and between open and closed VR sceneries. Similarly, HMD-based VR was used to generate visual stimuli and the effect of stimuli on postural control was evaluated under the conditions of eyes-open, eyes-closed, and three different VR designs; e.g., an optokinetic drum rotating around yaw, pitch, and roll axes, respectively ( 29 ). This research also reported differences between with and without VR environments in postural sway behavior of healthy YA.…”
Section: Discussionmentioning
confidence: 99%
“…We focused on analyzing velocity of postural sway because a meta-analysis found that significant differences were observed in sway velocity for an MCI group ( 13 ). In addition, a few studies developing a similar assessment system showed that sway speed was a sensitive dependent variable ( 28 , 29 ). We calculated the mean body sway velocity ( MV ) over 50 s after removing the initial 10 s of data to eliminate unusual movements caused by eye focus adjustment in the VR headset.…”
Section: Methodsmentioning
confidence: 99%